Adverse Life Events, Autoimmune Diseases and Fibromyalgia Among Women: Findings from the SAGA Cohort in Iceland - Nanna Margrét Kristinsdóttir 1993- (2020)
Background: Autoimmune diseases (ADs) and fibromyalgia (FMS) create a major public health problem due to disabling symptoms despite treatment and high prevalence. A dose-response relationship has been indicated in recent studies between the number of adverse life events and negative effects on health. The role of adversity in the onset of AD and FMS has been suggested, however, further research is needed. The aim of this study was to investigate the associations of number of adverse life events with AD, FMS and comorbid AD and FMS and possible moderating effects of demographic factors, social support and resilience. Methods: The SAGA Cohort is a nationwide population-based study where all women in Iceland (18-69 years old) were invited to participate in the years 2018-2019. In this cross-sectional study, data from the SAGA cohort was utilized. Women registered in the study via a web-based questionnaire, which was focused on trauma and overall health. The data retrieved for this study included measurements of adverse life events (measured by the Life Events Checklist), ADs, FMS, demographic variables, smoking, social support and resilience. Multiple Logistic Regression analysis was conducted to test the association of adverse life events with the studied outcomes, expressed as odds ratios (OR). Results: A total of 31.811 Icelandic women registered to the study and 26.861 finished answering the questionnaire, 88% had been exposed to at least one adverse life event. A total of 12% had an AD, 10% had FMS and 7% had both. Strong association was found between exposure to adverse life events and AD, FMS and comorbid AD and FMS. Those exposed to 6 or more adverse life events were around 2.5 times more likely to have an AD (OR, 2.41; 95% CI, 2.08-2.79), 5 times more likely to have FMS (OR, 5.24; 95% CI, 4.49-6.11) and 10.5 times more likely to have a comorbid FMS and AD (OR, 10.29; 95% CI, 8.70-12.52) compared to women exposed to 0-1 event. Social support appears to moderate the association of adverse life with ADs, but ...